Concept of God According to Moses Ben Maimon (1138-1204): Konsep Ketuhanan Menurut Musa Bin Maymun (1138-1204) - Senin, Nurhanisah; Wan Ramli, Wan Adli; Mohd Khambali @ Hambali, Khadijah (Afkar: Jurnal Akidah dan Pemikiran Islam, 2016)
This study aims to expound Maimonides’ discourse on the concept of God. Maimonides strongly emphasized a monotheistic belief of God through his logical arguments which was explicated extensively in his magnum opus The Guide of the Perplexed. Maimonides attempted to demonstrate that philosophy is readily imbued within the law. Hence, this paper will discuss Maimonides’ arguments on God’s existence, unity and incorporeality. In His existence, Maimonides advocated a dualistic approach to necessary existence as he affirmed that the universe was created however he suggested that it was created from eternal matter. In explaining His unity, Maimonides absolutely refuted subscribing attributes to God’s Essence. As for His incorporeality, anthropomorphistic verses must be understood in an equivocal form that demonstrates His incorporeality. In sum, Maimonides’ argument on the concept of God clearly resembles the philosophical work of the Aristotelian which affirmed God as the Intellect, Intelligen and Intelligible.